Competing hegemonic powers in the negotiating history of the GATT: an analysis of how the United States and United Kingdom's competing visions of the proposed multilateral trading regime influenced the final codification of the GATT - Rachwal, Natasha (Department of Private Law, 2021)
The General Agreement on Tariffs and Trade 1947 (hereafter referred to as the GATT) emerged in the aftermath of World War II and, despite the initial intention that it would serve as a mere interim arrangement while the administrative framework of the International Trade Organisation was finalised, the GATT would proceed to guide the course of multilateral trade throughout the twentieth century. What is often overlooked in mainstream analyses of the key principles underpinning the liberal international economic order is the significance of the negotiating history of the GATT which was dominated by two main participants, the United States and the United Kingdom. These parties experienced very different growth trajectories following World War II and so sought to advance different national interests within the negotiating forum. Briefly, while the United States was benefitting from an unprecedented increase in its economic and political power and wanted to see greater market access for its domestic industries, the United Kingdom was undergoing a difficult period of recovery and wanted to consolidate its system of imperial preferences. Nevertheless, because neither could unilaterally dominate the international policy space and because both recognised the value in promoting free trade for international political stability, they would ultimately reach a negotiated compromise resulting in the final codification of the GATT. In adopting a historical and textual methodology, this dissertation will argue that, in order to gain a more nuanced understanding of the principles underlying the GATT, one ought to examine the complexities of the negotiations leading up to its final codification, including the domestic interests advanced by the negotiating parties as well as contemporary hegemonic power dynamics.